2008
DOI: 10.1530/rep-07-0427
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of oestrogen receptors in the human corpus luteum

Abstract: The molecular mechanisms underlying the control of corpus luteum lifespan in women are not fully understood. Oestradiol has various luteolytic, or luteotrophic, functions in some species, and as it is synthesised within the human corpus luteum, it is an excellent candidate molecule to be a paracrine regulator of luteal function. This study aimed to comprehensively investigate the expression, regulation and effects of oestrogen receptors (ER) in human luteal cells. Genomic oestrogen receptors ERa, ERb1 and ERb2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…360 In luteinized human granulosa cells, Chiang et al found ERα levels to remain relatively constant over a period of 10 days in culture but always much lower than ERα mRNA levels. 398 Recent reports in human ovarian samples collected during elective hysterectomy demonstrate that ERα is expressed in granulosa cells of antral follicles, with weak to no positive immunohistochemical staining in luteinized granulosa cells 399 supporting previous data.…”
Section: Primatessupporting
confidence: 76%
See 1 more Smart Citation
“…360 In luteinized human granulosa cells, Chiang et al found ERα levels to remain relatively constant over a period of 10 days in culture but always much lower than ERα mRNA levels. 398 Recent reports in human ovarian samples collected during elective hysterectomy demonstrate that ERα is expressed in granulosa cells of antral follicles, with weak to no positive immunohistochemical staining in luteinized granulosa cells 399 supporting previous data.…”
Section: Primatessupporting
confidence: 76%
“…This study also used in vitro luteinized granulosa cells, treated with hCG or E2. Treatment of the luteinized granulosa cells with hCG reduced expression of ERα, ERβ1, and ERβ2 by approximately 50%, while treatment with E2 reduced expression of ERα and ERβ1 with no significant change in ERβ2, 399 suggesting that human granulosa cells may respond to LH by reducing ERβ in a manner similar to that found in rodent ovaries.…”
Section: Primatesmentioning
confidence: 69%
“…Nevertheless, the localization of both androgen receptors (AR) and Es receptors (ER) within the human CL (3,4) suggests a paracrine/autocrine role for these steroids in regulating luteal function (2).…”
mentioning
confidence: 99%
“…ERα, ERβ, and the plasma membrane estrogen receptor GPR30 have been reported in luteal tissues of rodents, domestic animals, monkeys, and women, with most studies suggesting that ERβ predominates (Duffy et al 2000, Hosokawa et al 2001, Diaz & Wiltbank 2004, Shibaya et al 2007, Wang et al 2007, van den Driesche et al 2008, Hazell et al 2009, Maranesi et al 2010). Additional studies have shown that estrogen acts directly at luteal cells to regulate functions as diverse as apoptosis, steroidogenesis, and inhibin production (Diaz & Wiltbank 2004, van den Driesche et al 2008). While expression of enzymes involved in estrogen synthesis increases as luteolysis approaches (Benyo et al 1993, Diaz & Wiltbank 2004), it is widely accepted that tissue estrogen concentrations within the corpus luteum are receptor-saturating throughout the luteal phase (Duffy et al 1999a).…”
Section: Discussionmentioning
confidence: 99%